Ski gliding technique on a quasi static laboratory device-comparison with the situation "on snow" and possibilities of performance enhancement - Kröll, J.; Stricker, G.; Mayrhofer, K.; Schwameder, H.; Müller, E. (ISBS - Conference Proceedings Archive (Konstanz), 2004)
The purpose of this paper is to introduce possibilities for the enhancement of the gliding performance in alpine ski racing using a specific gliding device. This device is used in our laboratory for evaluating and adjusting ski equipment on the one hand, and to give specific feedback on the athletes gliding technique on the other hand. Two independent studies will be presented to show transfer effects from the lab situation to the situation on snow. The first study examines the correlation between the force distribution while gliding on the device and gliding on snow (n=6 female elite skiers). Study two (experimental group n= 8; control group n=8) describes the changes of the force distribution on the device and the gliding time in a field test after 9 weeks of specific dry land training. The results of study 1 shows that the correlation between the situations is not as high as expected. The results from study 2 (significant change of force distribution on the device) show that we can quantify some relevant coordinative parameters of the gliding movement. One could conclude that performance diagnostics on the device is not sufficient to describe the complete gliding abilities of athletes. On the other hand athletes can use the device for specific coordination training, especially as it offers various options for feedback.